Colonoscopy findings in high-risk individuals compared to an average-risk control population. (July 2014) - Forsberg, Anna; Kjellström, Lars; Andreasson, Anna; Jaramillo, Edgar; Rubio, Carlos A.; Björck, Erik; Agréus, Lars; Talley, Nicholas J.; Lindblom, Annika
Abstract: Background and aims: There is clear evidence of reduced morbidity and mortality from regular colonoscopy programs in patients with Lynch syndrome (LS). Today, also individuals with empirically increased risks of colorectal cancer (CRC) are offered colonoscopic surveillance. The aim was to compare the findings at the first screening colonoscopy in LS carriers, and individuals with an increased risk of bowel cancer due to family history of CRC with a control population. Methods: Altogether 1397 individuals with an increased risk for CRC were divided in four risk groups: one with LS carriers and three groups with individuals with different family history of CRC. The findings were compared between the different risk groups and a control group consisting of 745 individuals from a control population who took part in a population-based colonoscopy study. Results: In LS, 30% of the individuals had adenomas and 10% advanced adenomas. The corresponding figures in the other risk groups were 14–24% and 4–7%, compared with 10% and 3% in the control group. The relative risk of having adenomas and advanced adenomas was, compared to controls, significantly higher for all risk groups except the group with the lowest risk. Age was a strong predictor for adenomas and advanced adenomas in both risk individuals and controls. Conclusions: Individuals with a family history of CRC have a high prevalence and cumulative risk of adenomas and advanced adenomas, and screening is motivated also in this risk group.